Melancolia, modernidade e sociedade contemporânea: um paralelo através da arte - Diniz, Gabriel Ferreira (2023)
The current work aims to understand how melancholy is represented in current society and in Contemporary Art, using art as a foundation for the theories addressed throughout the study. Here, art is seen as an area strictly related to social formation and individual awareness. To this end, the research initially addresses considerations of the concept of melancholy in philosophy and psychoanalysis, essential to understand how the melancholic state affects the individual. In this way, the writings of Aristotle and Freud are privileged. To transfer this discussion from the individual to the collective sphere, the second chapter observe the melancholy from its relationship with modernity. It is at this moment that we highlight the sociopolitical character of the melancholic state, based on the reading of Walter Benjamin's theses and the articulation between the romantic art movement and melancholy. The melancholic state comes to be understood as a feeling of revolt against modern society and capitalism. Finally, Bauman and Augé's theories about contemporary society reveal the perpetuation of exclusionary characteristics of modernity. When pondering the concept of decoloniality and analyzing Jean-Michel Basquiat's artistic production, we perceive the melancholy in denouncing the maintenance of a colonial project today. The methodology used is bibliographical survey and analysis of works of art